The Penal Code of the State of Minnesota 127, § 334 (1885) - (:unkn) unknown (My University, 1885)
§ 334: Prohibited the carry or possession with intent to use against another any slung-shot, sand-club, metal knuckles, dagger, dirk, knife, pistol, or other firearm, or any dangerous weapon. Violators guilty of misdemeanor.
Keywords: CARRY - INTENT TO COMMIT CRIME